Reappraising heme oxygenase-1 as a ferroptosis modulator in atherosclerosis: a mechanism-focused review - Xu, Jia; Chen, Che; Yuan, Han-Ying; Zhang, You-Yu; Wang, Chang-Rong; Xi, Xuan; Pan, Heng; Li, De-Hong; Lu, Yan (Frontiers in Immunology, 2026)
Atherosclerosis is the primary pathological basis of cardiovascular diseases, with macrophage dysfunction, lipid accumulation, and oxidative stress driving plaque formation and progression. Ferroptosis, an iron-dependent form of regulated cell death characterized by lipid peroxidation, has recently emerged as a pivotal mechanism influencing atherosclerosis. Heme oxygenase-1 (HO-1), a key regulator of heme catabolism and iron homeostasis, exerts dual roles in this process: moderate HO-1 activity confers cytoprotection through antioxidant effects, whereas excessive HO-1 expression promotes intracellular iron accumulation, oxidative stress, and ferroptotic cell death. In macrophages, HO-1 mediates both classical ferroptosis pathways via glutathione peroxidase 4 (GPX4) regulation and non-classical, erythrophagocytosis-induced ferroptosis, contributing to plaque instability. This review systematically examines the molecular mechanisms underlying HO-1-induced ferroptosis in atherosclerosis, emphasizing its interplay with iron metabolism, oxidative stress, and macrophage function. Understanding the context-dependent effects of HO-1 provides novel insights into the regulation of vascular cell fate and plaque stability, highlighting potential therapeutic targets for the prevention and treatment of atherosclerotic cardiovascular diseases.